Analisis Faktor Penyebab Kesulitan Membaca Permulaan Pada Siswa Kelas II Sekolah Dasar - Putri Adrian; Chairun Nisa; Chandra Chandra; Tiok Wijanarko (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the factors that cause initial reading difficulties in second grade elementary school students and the solutions that can be provided. The approach used in this research is qualitative with descriptive methods. The subjects of this research were second grade elementary school students. Data collection techniques include observation, interviews and documentation. Analysis techniques include data reduction, data presentation, and drawing conclusions or verification. Based on the research results, the factors causing the difficulties students experience in reading are a lack of guidance and concern from parents, a lack of reading learning activities at home and at school, and a lack of interest in learning within the students themselves.